(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Tkachuk S. І. Features of preparing and professional activity of teachers of technologies in the conditions of informatization of education. In this article the features of training and professional work of teachers in terms of information technology education is shown, methodological potential of innovative technologies and their introduction during independent work of future specialists are highlighted.